Psychometric properties, stability, and predictive validity of the Korean version of the Prolonged Grief Disorder Scale (PG-13-K): A longitudinal study among bereaved Koreans. Issue 4 (21st April 2023) - Hwang, Yujin; Lee, Dong Hun; Prigerson, Holly G.
Abstract: This study aims to investigate the psychometric properties, stability, and predictive validity of the PG-13-K. Two subsamples were used: the first subsample ( N = 153), participated at Time 1 only, and the second subsample ( N = 184) participated at both Time 1 and Time 2. At each time point, reliability, test-retest reliability, and validity were adequate, and the hypothesized two-factor model indicated good to excellent fit. Moreover, the PG-13-K was able to predict the correlation between prolonged grief disorder (PGD) and negative psychological factors. The PG-13-K is a useful and valid instrument for measuring PGD symptoms in Korean settings.